Study on antimony mobility in a contaminated shallow lake sediment using the diffusive gradients in thin films technique. (March 2021) - Yao, Cheng; Che, Feifei; Jiang, Xia; Wu, Zhihao; Chen, Junyi; Wang, Kun
Abstract: Antimony is a priority environmental contaminant. Increasing attention is being paid to the behaviors and mobilities of the various Sb species in the environment. Sb speciation in the environment and the mobilities of Sb species at mining sites have been studied well, but Sb speciation and mobility in shallow lakes requires further study. Here, we studied Sb behavior in sediment of a shallow lake in the plain rivers network in Taihu Basin that suffers continual Sb inputs from textile plants. The diffusive gradients in thin films techniques (DGT) made of zirconium oxide based binding resin gel (ZrO-Chelex), agarose diffusive gel and polyvinylidene fluoride filter were deployed in water and sediment to obtain a high-resolution record in situ. The results indicated that (1) pollutants released by textile plants caused relatively high Sb(Ⅲ), Sb(Ⅴ) and organoantimony concentrations in the eutrophic shallow lake, (2) Sb was seldomly mobile in the oxic layer where Sb(Ⅲ) was sorbed on Fe(Ⅲ) oxides and gradually formed Fe–Sb complexes in the sediment, but in the anoxic environment (oxidation-reduction potential: 366 − −344 mv) Sb(V), Fe(Ⅱ) and P (V) were simultaneously released to resupply the porewater, (3) the release of Sb from solid phase is decided by the redox condition, and the rate of release is dependent on the labile Sb content of the sediment. The mobility of Sb should be given sufficient attention when the potential ecological risk of metal(loid)s in shallow lakes and wetlands sediment are evaluated. Highlights: Environmental behavior of Sb contaminants in a shallow lake were illustrated. The DGT was deployed in lake to record the mobility of Sb. The anoxic condition in sediment was in favor of dissolution of Fe–Sb complexes.